Perlindungan Hukum Terhadap Hak Tetangga Akibat Dampak Rumah Walet di Pemukiman kota Palopo - M. Ardiansyah WH; Abdain; Takdir (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study examines the legal protection of residents, particularly neighbors' rights, against the impact of swiftlet houses in residential areas in Palopo City. This phenomenon is controversial because the establishment of swiftlet houses in residential areas often causes noise, air pollution, spatial inconsistencies, house damage, the potential spread of disease, and even affects property sales values. Although regulations prohibit or restrict such activities, particularly near educational and public facilities, these swiftlet houses continue to be established. In Islam, neighbors hold a vital position and must be treated well, as recommended by the Prophet Muhammad (peace be upon him). The purpose of this study is to analyze the forms of legal protection for local residents regarding the presence of swiftlet houses in residential areas, and the extent to which the government enforces established regulations. This study used a qualitative approach with in-depth interviews and participatory observation. The results indicate that the Palopo City Government is still not optimal in enforcing regulations related to swiftlet house businesses. Lack of understanding, coordination between regional agencies, and weak law enforcement have resulted in a lack of legal certainty for affected communities. The conclusion of this study is that legal protection for residents can be achieved through consistent law enforcement, tightened licensing procedures, and the application of legal principles such as the principle of "sic utere tuo ut alienum non laedas" (use your rights without harming the rights of others). Thus, the swiftlet house business can continue to operate without compromising residents' rights to a healthy and comfortable environment.